Darwinism in economics and the evolutionary theory of policy-making - Christian Schubert (Max Planck Institute of Economics, 2009)
According to the advocates of a Generalized Darwinism (GD), the three core Darwinian principles of variation, selection and retention (or inheritance) can be used as a general framework for the development of theories explaining evolutionary processes in the socioeconomic domain. Even though these are originally biological terms, GD argues that they can be re-defined in such a way as to abstract from biological particulars. We argue that this approach does not only risk to misguide positive theory development, but that it may also impede the construction of a coherent evolutionary approach to policy implications. This is shown with respect to the positive, instrumental and normative theories such an approach is supposed to be based upon.
Keywords: A1; B4; B52; D6; 330; Evolution; Selection; Darwinism; Ontology; Continuity Hypothesis; Evolutionary Theory of Policy-Making